Modulação da memória emocional em camundongos: análise da interação dos sistemas histaminérgico e colinérgico na amídala - Fernandes, Carlos Eduardo Monici (Universidade Federal de São Carlos, 2015)
This study investigated the effects of bilateral intra-amygdala microinjections of PNU-282987, which is a nicotinic cholinergic agonist, on anxiety and emotional memory as well as the reversal of amnesia induced by an H1 histaminergic antagonist (CPA) in mice subjected to the elevated plus-maze (EPM). For this purpose, two experiments were performed. The subjects were seventynine adult male Swiss mice weighing 25-40g at testing. Behavioral testing was performed on two consecutive days (T1 and T2). In both experiments, the drugs were administered prior to testing. In Experiment 1, the animals received bilateral microinjections of saline (SAL) or PNU-282987 (0.1 nmol) and four experimental groups were tested; i.e., SAL-SAL, SAL-PNU, PNU-SAL and PNU-PNU groups. In Experiment 2, the animals received combined bilateral microinjections of CPA (0.16 nmol) and PNU-282987 on T1 and they were re-exposed to the EPM 24 hours later. Four experimental groups were tested; i.e., SAL-SAL, PNU-SAL, CPA-SAL and CPA-PNU groups. ANOVA followed by Duncan´s tests revealed no significant differences between the SAL and treated groups at T1 in the measurements of anxiety (i.e., % open arm entries and % open arm time, ANOVA, p > 0.05), which indicates that the CPA and PNU did not induce effects on anxiety. The isolated microinjections of PNU-282987 did not produce effects on emotional memory; however, the combined microinjections of PNU-282987 and CPA were able to reverse the deficit in memory induced by CPA (ANOVA, p < 0.05). There were no significant changes in the numbers of enclosed arm entries which served as a measure of locomotor activity (ANOVA, p > 0.05). Taken together, these results suggest that intra-amygdala injections of PNU-282987 did not induce effects on anxiety and emotional memory per se; however, the combined injections of CPA and PNU-282987 reversed the amnesic effects caused by CPA, which is suggestive of an interaction between the histaminergic and cholinergic systems in the modulation of emotion memory acquisition in mice subjected to the EPM.
Keywords: Fisioterapia; Clorfeniramina; PNU-282987; Memória emocional; Amídala; Labirinto em cruz elevado; Camundongo; Chlorpheniramine; Emotional memory; Amygdala; Mice; Elevated plusmaze; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL